Early Childhood Curiosity In Books “Kau Sedang Apa, Lala?” By Widya Ross - Widhyastuti , Ari (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
This research aims to describe the value of character education contained in the book '